Equal Force Recovery in Dysferlin-Deficient and Wild-Type Muscles Following Saponin Exposure. (18th September 2011) - Zhao, Piming; Xu, Li; Ait-Mou, Younss; de Tombe, Pieter P.; Han, Renzhi
Abstract : Dysferlin plays an important role in repairing membrane damage elicited by laser irradiation, and dysferlin deficiency causes muscular dystrophy and associated cardiomyopathy. Proteins such as perforin, complement component C9, and bacteria-derived cytolysins, as well as the natural detergent saponin, can form large pores on the cell membrane via complexation with cholesterol. However, it is not clear whether dysferlin plays a role in repairing membrane damage induced by pore-forming reagents. In this study, we observed that dysferlin-deficient muscles recovered the tetanic force production to the same extent as their WT counterparts following a 5-min saponin exposure (50  μ g/mL). Interestingly, the slow soleus muscles recovered significantly better than the fast extensor digitorum longus (EDL) muscles. Our data suggest that dysferlin is unlikely involved in repairing saponin-induced membrane damage and that the slow muscle is more efficient than the fast muscle in repairing such damage.